Análise comparativa de conversores monofásicos aplicados a correção de fator de potência - Beltrame, Fernando (2009)
This work presents a study and a comparative analysis of high power single-phase converter applied to power factor correctioii in according to the international standards IEC 61000-3-4 (harmonics limitation) and CISPR 22 (electromagnetic interference limitation) for high power applications. The converters studied were the conventional boost converter, the interleaved boost converter, with two cell operating with a delay angle of 180" between each other, and the dual boost converter. Such converters are used in front-end modules of information technology equipment. AI1 converters have the same input and output voltage and the same input current. The converters were projected to provide the same total input harmonic distortion (THD), with the idea of using the same input filter. Implementation of the control laws was performed through a digital control with the use of a 16 bits microcontroller. A11 converters were, first of all, studied and presented in this dissertation. The analyzed parameters for comparison were: power factor, total harmonic distortion (THD), semiconductor losses and magnetic losses, heat-sinks volume and magnetics volume, conducted electromagnetic interference, performance and costs.